System reliability-based bridge assessment using the response surface method - Onoufriou, Toula; Jo, SungIl; Crocombe, Andrew D. (My University, 2005)
The resistance response surface method (RSM) is known to be a powerful tool for the evaluation of failure probability of complex structures such as bridges. The resistance RSM is addressed in detail in this paper. Loading models for the reliability-based bridge assessment were also addressed. Some assumptions on the traffic loading were made in order to simplify the loading conditions. An actual UK bridge was used as a numerical example. Reliability analyses show that the reliability of a bridge model is dominated mainly by the reliability for a two-lane loading case.
Keywords: Structural analysis (Engineering); Concrete bridges; Reliability